Association of CHA2DS2-VASC Score with in-Hospital Cardiovascular Adverse Events in Patients with Acute ST-Segment Elevation Myocardial Infarction - Caoyang Fang; Zhenfei Chen; Jing Zhang; Xiaoqin Jin; Mengsi Yang (International Journal of Clinical Practice)
Background. Acute ST-elevation myocardial infarction (STEMI) is a common clinical critical illness, and accurate, reliable, simple, and easy-to-remember tools are needed in clinical practice to quickly identify the risk of this condition in STEMI patients. This study investigates the predictive value of the admission CHA2DS2-VASc score for in-hospital MACE in STEMI patients. Methods. A total of 210 STEMI patients who visited the Chest Pain Center of the Second People‘s Hospital of Hefei from December 2019 to December 2021 were retrospectively analyzed. They were divided into MACE and non-MACE groups. The receiver operating characteristic curve (ROC) was used to assess the predictive value of the CHA2DS2-VASc score for MACE events during hospitalization. Results. The CHA2DS2-VASc score was higher in the MACE group than in the non-MACE group (P<0.05), and multivariate logistic regression analysis showed that the CHA2DS2-VASc score was an independent risk factor for MACE events during hospitalization in STEMI patients (OR = 1.391, 95%CI 1.044–1.853, P=0.024); ROC curve analysis showed that the area under the curve (AUC) of the CHA2DS2-VASc score was 0.744, the sensitivity was 0.64, the specificity was 0.694, and the optimal cutoff value was 3.5 in predicting the risk of MACE events during hospitalization in STEMI patients. There were no significant differences between the GRACE score (0.744 VS.0.827) and TIMI score (0.744VS.0.745) (P>0.05). Conclusion. The CHA2DS2-VASc score can successfully predict the occurrence of in-hospital MACE events in STEMI patients.